A Tale of 2 Constituencies: Exploring Patient and Clinician Perspectives in the Age of Big Data. Issue 10 (October 2018) - Goytia, Crispin N.; Kastenbaum, Isaac; Shelley, Donna; Horowitz, Carol R.; Kaushal, Rainu
Abstract : Background: Patient and clinician stakeholders are inadequately engaged in key aspects of research, particularly regarding use of Big Data to study and improve patient-centered outcomes. Little is known about the attitudes, interests, and concerns of stakeholders regarding such data. Research Design: The New York City Clinical Data Research Network (NYC-CDRN), a collaboration of research, clinical, and community leaders built a deidentified dataset containing electronic health records from millions of New Yorkers. Guided by a patient-clinician advisory board, we developed a question guide to explore patient and clinician experiences and ideas about research using large datasets. Trained facilitators led discussions during preexisting patient, community, and clinician group meetings. The research team coded meeting notes and identified themes. Results: Fully 272 individuals participated in 19 listening sessions (139 patients/advocates, 133 clinicians) at 6 medical centers with diverse NYC communities: 76% were female and 63% were nonwhite. Clinicians and patients agreed on all major themes including the central role of clinicians in introducing patients to research and the need for public campaigns to inform stakeholders about Big Data. Stakeholders were interested in using granular data to compare the care and clinical outcomes of their neighborhoods with others across NYC, but were also concerned that data could not truly be deidentified. Conclusions: Clinicians and patients agree on potential benefits of stakeholder-engaged Big Data research and provided suggestions for further research and building stakeholder research capacity. This evaluation demonstrated the potential of brief meetings with existing patient and clinical groups to explore barriers and facilitators to patient and clinician engagement.